Implementasi Sistem Informasi Manajemen dalam Mendukung Pelayanan Administrasi di SMA Negeri 1 Barru - Musdalifah Musdalifah; Nasir Mahmud; Kasmawati Kasmawati (Kelola: Journal of Islamic Education Management, 2019)
This study aimed to determine the implementation of system information management and administrative services at SMA Negeri 1 Barru. This research is a field research using qualitative methods and qualitative approaches. Data collection techniques used were interviews and observation. The results showed that the application of management information systems in supporting administrative services at SMA Negeri 1 Barru had been well implemented by utilizing all facilities and infrastructure facilities as a foothold in optimizing the application of system information management.